Echovirus 6 associated to aseptic meningitis outbreak, in São Joaquim da Barra, São Paulo, Brazil - Luchs,Adriana (2008)
An aseptic meningitis outbreak occurred during a period from February to May 2004 in São Joaquim da Barra, a town in the northern region of São Paulo State. A total of 40 cases were reported to the Epidemiological Surveillance Center of São Paulo State. Cerebrospinal fluid samples obtained from 23 patients were sent to the Adolfo Lutz Institute for isolation of the virus. These samples were inoculated into RD, HEp2 and Vero cell lineages and those presenting a cytopathogenic effect were selected for analysis by indirect immunofluorescence assay (IFA), neutralization testing (Nt) and reverse transcriptase-polymerase chain reaction (RT-PCR). Cytopathogenic effects were observed in 52.2% (12/23) of these samples. All isolated viruses were identified as human enterovirus by IFA and RT-PCR and echovirus 6 was typed by IFA and Nt. Our results confirmed the participation and importance of echovirus as the etiological agent responsible for this outbreak and the serotype diversity of human enteroviruses circulating in São Paulo State.